2019
DOI: 10.1071/sr18113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crop production practices on soil characteristics and metabolic diversity of microbial communities under winter wheat

Abstract: The aim of this research was to compare the effects of organic (ORG, no mineral fertilisers and pesticides) and conventional (CON, with mineral fertilisation and plant protection chemicals) crop production systems on some soil properties: soil organic matter (SOM) and particulate organic matter (POM) contents, dehydrogenase activity and metabolic microbial diversity (Biolog EcoPlate™). Samples of Haplic Luvisol soil were collected from 23-year-old experimental fields under winter wheat from the depth layers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…The above findings are similar to the results published by many researchers, including [7,22,40], who found that organic management significantly increased OM concentration in surface soil compared with conventional farming system. Moreover, Sarkar et al [60] reported that OM concentration in soil within cultivated fields was significantly lower than within uncultivated fields and the decrease of OM was mainly due to the tillage practices.…”
Section: Effects On Soil Organic Mattersupporting
confidence: 91%
See 4 more Smart Citations
“…The above findings are similar to the results published by many researchers, including [7,22,40], who found that organic management significantly increased OM concentration in surface soil compared with conventional farming system. Moreover, Sarkar et al [60] reported that OM concentration in soil within cultivated fields was significantly lower than within uncultivated fields and the decrease of OM was mainly due to the tillage practices.…”
Section: Effects On Soil Organic Mattersupporting
confidence: 91%
“…The above findings are similar to the results published by many researchers, including [7,22,40], who found that organic management significantly increased OM concentration in surface soil The tilled soil under the ORG crop production system showed similar trends in OM content as non-tilled soil under PRG. At depths of 0-5 and 5-10 cm the OM content in soil under the ORG system and PRG was significantly higher compared with the CON system; however, no significant differences were found between ORG and PRG treatments.…”
Section: Effects On Soil Organic Mattersupporting
confidence: 91%
See 3 more Smart Citations